2016
DOI: 10.1016/j.powtec.2016.04.052
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lifter shape and operating parameters on the flow of materials in a pilot rotary kiln: Part III. Up-scaling considerations and segregation analysis

Abstract: Up-scaling tracer experiments were carried out in a pilot-scale rotary kiln twice as big as the kiln used in the first two Parts of this study. Internal fixtures such as grid, or lifter structure arranged in 3 and 6 rows of single throughout lifters were used. The effects of these removable fixtures and other usual operating conditions, namely, mass flow rate of granular biomass materials, rotational speed and slope of the kiln on the residence time distribution (RTD), the mean and variance of residence time (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
4
13
0
Order By: Relevance
“…When the incline angle increases, the residence time of particles decreases and RTD becomes narrower. Previous studies similarly showed that RTD becomes narrower when incline angle increases [7,10,24,33]. Figure 5f compares the RTD results of 6 mm at two different flow rates.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…When the incline angle increases, the residence time of particles decreases and RTD becomes narrower. Previous studies similarly showed that RTD becomes narrower when incline angle increases [7,10,24,33]. Figure 5f compares the RTD results of 6 mm at two different flow rates.…”
Section: Resultssupporting
confidence: 54%
“…A narrower distribution is obtained due to higher rotation speed. Other researchers have also shown that narrower RTD are obtained when rotation speed increases [5,7,10,24,[31][32][33]. Figure 5e shows the effect of the incline angle on the RTD.…”
Section: Resultsmentioning
confidence: 70%
“…According to the results, the number of lifters and longer residence time increase the axial mixing. The increase of lifters for improving mixing was also noted by Bongo Njeng et al (2016). The positive effect to axial mixing by increasing residence time or drum length is explained by dispersion time increase (Fogler, 2006).…”
Section: Resultsmentioning
confidence: 78%
“…The influence of the operating parameters, namely the mass flow rate, the exit dam height and the lifter hold-up capacity on the w-t-s heat transfer coefficient were analyzed with the use of the filling degree, as the filling degree has been found to increase with these operating parameters [49,50,51]. Figure 10 shows the variation of the w-t-s heat transfer coefficient with the filling degree following a variation of the mass flow rate, the exit dam height and the lifter hold-up capacity.…”
Section: Effect Of Operating Parametersmentioning
confidence: 99%